Special Issue: 2019 Research Data Access and Preservation Summit - Tina Griffin; Rebekah Kati; Alicia Krzton; Lora Leligdon (Journal of eScience Librarianship, 2020)
The Journal of eScience Librarianship has partnered with the Research Data Access & Preservation (RDAP) Association for a second year to publish selected conference proceedings. This issue highlights the research presented at the RDAP 2019 Summit and the community it has fostered.